Geronimo Stilton : Mighty Mount Kilimanjaro - Stilton, Geronimo; Ronchi, Roberto; Bigolin, Silvia (New York : Scholastic, 2010)
Bruce Hyena convinces Geronimo to join him in climbing Mount Kilimanjaro, a task for which the mouse journalist is completely unprepared.
Keywords: Mice -- Fiction; Detective and mystery stories; Mountaineering -- Fiction; Stilton, Geronimo (Fictitious character) -- Fiction; Mice -- Fiction; Mountaineering -- Fiction; Mystery and detective stories; Kilimanjaro, Mount (Tanzania) -- Fiction; Mystery fiction